Can Antidiabetic Drugs Improve Male Reproductive (Dys)Function Associated with Diabetes? - Tavares, R.S.; Escada-Rebelo, S.; Sousa, M.I.; Silva, A.; Ramalho-Santos, J.; Amaral, S. (Current Medicinal Chemistry, 2019)
The alarming increase in the number of diabetic patients worldwide raises concerns regarding the impact of the disease on global health, not to mention on social and economic aspects. Furthermore, the association of this complex metabolic disorder with male reproductive impairment is worrying, mainly due to the increasing chances that young individuals, at the apex of their reproductive window, could be affected by the disease, further contributing to the disturbing decline in male fertility worldwide. The cornerstone of diabetes management is glycemic control, proven to be effective in avoiding, minimizing or preventing the appearance or development of disease-related complications. Nonetheless, the possible impact of these therapeutic interventions on male reproductive function is essentially unexplored. To address this issue, we have made a critical assessment of the literature on the effects of several antidiabetic drugs on male reproductive function. While the crucial role of insulin is clear, as shown by the recovery of reproductive impairments in insulin-deficient individuals after treatment, the same clearly does not apply to other antidiabetic strategies. In fact, there is an abundance of controversial reports, possibly related to the various study designs, experimental models and compounds used, which include biguanides, sulfonylureas, meglitinides, thiazolidinediones/glitazones, bile acid sequestrants, amylin mimetics, as well as sodiumglucose co-transporter 2 (SGLT2) inhibitors, glucagon-like peptide 1 (GLP1), α-glucosidase inhibitors and dipeptidyl peptidase 4 (DPP4) inhibitors. These aspects constitute the focus of the current review.
Keywords: reproductive dysfunction